Pendampingan KWT Melati Melalui Pemanfaatan Platform E-Commerce Sebagai Sarana Pemasaran Di Desa Surana Kabupaten Lombok Barat - Mulyawati, Sri; Apriana Hidayanti, Anna; Nur Sindy Setiawan, Rifani; Anwar, Anwar (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Electronic commerce, abbreviated as e-commerce, is an electronic trading platform that must be connected to the internet. E-commerce has many benefits for businesses and consumers. The number of e-commerce users has increased along with the increasing number of internet users in Indonesia. However, in some areas, there are still people who do not understand e-commerce. KWT Melati, located in Suranadi Village, West Lombok Regency, conducts traditional marketing, because it does not recognize e-commerce. KWT members find it difficult to adapt to technological developments, and a few of them are passive users of e-commerce applications, namely only as consumers. Therefore, the purpose of this service activity is to assist KWT Melati through the utilization of e-commerce platforms as a means of promotion. The service method consists of a pre-activity survey, socialization, mentoring, and evaluation. The number of activity participants was 20 people who were active members of KWT Melati. The results of the service activities show that participants have understood and are able to use e-commerce, in this case, the Shopee application